2022
DOI: 10.1002/sus2.60
|View full text |Cite
|
Sign up to set email alerts
|

Regulating closed pore structure enables significantly improved sodium storage for hard carbon pyrolyzing at relatively low temperature

Abstract: The closed pore has been considered as the key structure for Na ion storage in hard carbon. However, the traditional view is that closed pores can only be formed by the curling of graphite-like crystallites in the case of high temperature carbonization. Ingenious designing of closed pore structures at lower temperature is still blank. Herein, for the first time, engineering the wall thickness and number of closed pores in waste rosewood-derived hard carbon was successfully achieved at a low temperature of 1100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 46 publications
1
10
1
Order By: Relevance
“…A large body of research suggests that closed pores (inaccessible by gases) in disordered carbons play a crucial role in the storage of sodium. [31][32][33][34] Distinct from N 2 adsorption/desorption measurement, in which it is difficult to detect closed pores in carbons, small-angle X-ray scattering (SAXS) can provide information on full pores including both open and closed pores. 30 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A large body of research suggests that closed pores (inaccessible by gases) in disordered carbons play a crucial role in the storage of sodium. [31][32][33][34] Distinct from N 2 adsorption/desorption measurement, in which it is difficult to detect closed pores in carbons, small-angle X-ray scattering (SAXS) can provide information on full pores including both open and closed pores. 30 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Zhou et al. [ 194 ] prepared HC from rosewood (pre‐chemically treated or not) at 1100 °C and found that the chemical treatment led to a larger volume of closed pores compared to the untreated HC (i.e., 0.055 cm 3 g −1 vs. 0.039 cm 3 g −1 ). The higher volume of closed pores was related to the breakdown of the fibrous structure of the precursor (i.e., the elimination of hemicellulose/lignin and the partial hydrolysis of cellulose in an alkaline medium), which resulted in the development of closed pores with thinner walls.…”
Section: Relationship Between Synthesis Parameters and Hard Carbon Pr...mentioning
confidence: 99%
“…When placed in a subzero-temperature environment, the SIBs suffer from severe energy and power losses, resulting in unsatisfactory electrochemical performance, mainly due to the sluggish diffusion kinetics of sodium ions and electrons at LTs. Besides, the interfacial problems including sluggish interfacial electrochemical reaction kinetics, poor interfacial ion storage capacity will continue to be exacerbated at LTs. It is urgent to exploit appropriate means to improve the interface problem at LTs. The application of interfacial chemical bonding in electrochemical storage and energy conversion systems is developed, therein special bridging bonds of M–X–C (M presents metal elements; X = O, S, N, etc.…”
Section: Introductionmentioning
confidence: 99%